2012
DOI: 10.1002/kin.20748
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline hydrolysis of ethiofencarb: Kinetic study and mechanism degradation

Abstract: The present paper deals with the hydrolysis of ethiofencarb [2ethylthiomethyl(phenyl)-N-methylcarbamate] in alkaline solution. The reaction kinetics has been investigated using spectrophotometric and liquid chromatographic techniques. The rate constants were determined following a proposed first-order kinetic model. The positive activation entropy S = = +100.07 J mol −1 K −1 and the absence of general basic catalysis indicated an E1cB hydrolytic mechanism, involving the formation of methyl isocyanate. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…The positive value of the activation entropy is in agreement with the mechanism E1cB. Comparable values were obtained for the hydrolysis reaction of a series of N ‐methylcarbamates studied in our laboratory: carbaryl , carbofuran , methiocarb , bendiorab , zectran , aminocarb , landrin , ethiofencarb , carzol , and isoprocarb .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The positive value of the activation entropy is in agreement with the mechanism E1cB. Comparable values were obtained for the hydrolysis reaction of a series of N ‐methylcarbamates studied in our laboratory: carbaryl , carbofuran , methiocarb , bendiorab , zectran , aminocarb , landrin , ethiofencarb , carzol , and isoprocarb .…”
Section: Resultssupporting
confidence: 81%
“…The positive value of the activation entropy is in agreement with the mechanism E1cB. Comparable values were obtained for the hydrolysis reaction of a series of N-methylcarbamates studied in our laboratory: carbaryl [3], carbofuran [4], methiocarb [5], bendiorab [6], zectran [7], aminocarb [8], landrin [9], ethiofencarb [10], carzol [11], and isoprocarb [12]. The Brönsted line log k OH = β pK a + cte, which relates the logarithm of the bimolecular rate constant to the pK a of the leaving group, can be used to elucidate the mechanism of the BDMC hydrolysis.…”
Section: Effect Of Temperaturesupporting
confidence: 76%
See 1 more Smart Citation
“…So there is no general base catalysis and the E2 mechanism can be eliminated. These results are consistent with those obtained for bendiocarb, Zectran, methiocarb, ethiofencarb and landrin [22][23][24][25].…”
Section: Possibility Of a Bimolecular Elimination Reaction E2 -Searchsupporting
confidence: 92%
“…The main pathway of this transformation is hydrolysis since the common structural feature of N-methylcarbamates is a N-methyl group that can be easily hydrolysed to form methylamine and the corresponding phenols in alkaline media. Consequently we have undertaken a study of the determination of both kinetic and mechanistic aspects of the hydrolysis of PNMCs such as carbaryl [3], carbofuran [4], methiocarb [5], bendiocarb [6], aminocarb [7], zectran [8] and landrin [9]. We showed that hydrolysis of PNMCs exhibited pseudo-first order kinetics with respect to substrate in aqueous media.…”
Section: Introductionmentioning
confidence: 99%